The Impact of terrorism on economic activity in Iraq during the period(2004-2013) - Ali, Haider (The Gulf Economist, 2022)
The phenomenon of terrorism in Iraq during the past two decades has attracted increasing attention from the Iraqi government. Indeed, terrorism has become one of the most serious problems facing the economy. The economy has incurred many direct and indirect costs, and damaged the infrastructure in most of Iraq’s governorates, and caused destruction to various economic sectors, including In agriculture, industry and the service sector, there is a strong relationship between political stability on the one hand and the paths of economic development on the other, and therefore it can be said that terrorism is one of the most important challenges facing the economy because of the direct threat of terrorism represented in hitting the national economy, from this point of view comes the importance of this Research to clarify the economic effects of the phenomenon of terrorism on the overall economic activity as well as the effects caused by terrorism on the underlying structures and economic sectors and the accompanying increase in security and defense expenditures.